2020
DOI: 10.37506/ijfmt.v14i2.3109
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses’ Knowledge toward Nursing Intervention for Eye Trauma at Baghdad Teaching Hospitals

Abstract: Nurses in emergency care for eye trauma usually concentrate on life threatening issues which are emergency in most situations that lead to little concern of the less emergency issues like eye problems even it is serious problem. Objectives: Assessment of Nurses' Knowledge toward Nursing Intervention for Eye Trauma and to find out a relationship between nurses knowledge with some variables such as (educational level, year of experience in hospital, training course).Methodology: A descriptive study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Data were gathered using a questionnaire and a random sample technique. These findings indicated that Saudi citizens need to be more knowledgeable about appropriate first aid in cases of ocular injury [7].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Data were gathered using a questionnaire and a random sample technique. These findings indicated that Saudi citizens need to be more knowledgeable about appropriate first aid in cases of ocular injury [7].…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, another study conducted in Baghdad acquired ocular first-aid knowledge among emergency room nurses. It showed that regardless of the nurses' sufficient information about eye injuries, they required additional education or training programs to enhance their expertise [7].…”
Section: Introductionmentioning
confidence: 99%